(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2016)
This paper examines Mediation as an Alternative Dispute Resolution process [ADR] in light of its “multi-level” legal scheme, namely the Directive 2008/52/EC, the Act 5/2012 and the autonomic laws. These Acts provide a concept of mediation and identify its main principles (i. e. voluntariness, confidentiality, impartiality and neutrality). There is, however, an interesting paradox: despite the well-known advantages of mediation (it entails an economical procedure and affords adequate satisfaction to the parties), it remains underused in the European jurisdictions. This paper calls, therefore, for measures to encourage its use, such as an adequate training for lawyers as to the appropriate manner in which to provide advice during the procedure.